1993
DOI: 10.1002/jlb.54.5.384
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide and a phorbol ester stimulate secretion of tumor necrosis factor-α from alveolar macrophages through action on overlapping subsets of cells

Abstract: A cell-by-cell analysis of the secretory ability of stimulated, individual alveolar macrophages (AMs) was performed through use of a tumor necrosis factor alpha (TNF-alpha) reverse hemolytic plaque assay. Two functional end points were measured: the percentage of AMs that were TNF-alpha secretors and the cumulative amount of TNF-alpha secreted by AMs (average plaque area, microns 2). Lipopolysaccharide (LPS; 100 micrograms/ml) increased cumulative TNF-alpha release at both 7 and 20 h of incubation. On the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…More than 10 yr ago, Murphy and Herscowitz reported functional variability and subpopulations at differing stages of maturity among AM isolated from rabbits (18). From analyzing TNF production by individual porcine AM treated with LPS or phorbol ester, Taylor and colleagues have more recently shown that particulm" smaU subsets of AM respond to distinct stimuli (27), Thus, the variations observed with these AM cell lines most likely reflect the heterogeneity of the original pool of primary cells from which they were derived.…”
Section: Synopsismentioning
confidence: 97%
“…More than 10 yr ago, Murphy and Herscowitz reported functional variability and subpopulations at differing stages of maturity among AM isolated from rabbits (18). From analyzing TNF production by individual porcine AM treated with LPS or phorbol ester, Taylor and colleagues have more recently shown that particulm" smaU subsets of AM respond to distinct stimuli (27), Thus, the variations observed with these AM cell lines most likely reflect the heterogeneity of the original pool of primary cells from which they were derived.…”
Section: Synopsismentioning
confidence: 97%
“…There have been numerous studies of pig macrophage responses to activation that largely recapitulate findings from mouse or human systems. Porcine macrophages from various locations treated with LPS increase production of the major proinflammatory cytokine TNF-␣ [152][153][154] and expression of IL-1␤ [149,155,156], IL-6 [157,158], IL-8 [159,160], and IL-12 [155,161]. Useful microarray platforms are in their comparative infancy in pigs (see below) but have already been used in a study of transcriptional responses within the LNs of pigs infected with salmonella [90] and with monocytes infected with African swine fever virus [162].…”
Section: Inflammatory Cytokine Production In Pigsmentioning
confidence: 99%
“…Luteal tissue was then dispersed, and a TNFa-RHPA was performed [20]. Briefly, the luteal cells (0.25 X 10 6 cells/ml) were mixed 1:1 with a 12% suspension of ovine red blood cells to which Protein A (Sigma, St. Louis, MO) had been attached by the chromium conjugation method, and this mixture was placed in incubation chambers (Cunningham chambers).…”
Section: Rhpamentioning
confidence: 99%